Factors That Influence Turnover Intention at PT XYZ - Alvin Paulus Silitonga; Achmad Ghazali (Eduvest - Journal of Universal Studies, 2025)
High employee turnover rates represent a critical challenge in human resource management, particularly in joint venture companies operating in the power generation sector, where maintaining workforce stability is essential for operational excellence and technology transfer. Therefore, this research aims to analyze the influence of these two variables on turnover intention by considering important dimensions such as conditions for engagement, opinion engagement, engagement behavior, career development, work environment, employee relationships with management, and compensation and benefits. The study employs a mixed-methods approach, combining Partial Least Squares Structural Equation Modeling (PLS-SEM) for quantitative analysis with in-depth qualitative interviews to provide comprehensive insights. The quantitative findings reveal that job satisfaction (β = -0.578, p < 0.001) exerts a stronger negative influence on turnover intention compared to employee engagement (β = -0.382, p < 0.001), collectively explaining 70.2% of the variance in turnover intention (R² = 0.702). Specifically, career development, work environment, and employee relationships with management emerged as significant predictors of turnover intention, while opinion engagement showed no significant direct effect. Qualitative insights revealed underlying issues, including unclear certification pathways, cultural and communication barriers between local and expatriate staff, insufficient management support during high-pressure situations, and perceived inequities in compensation structures. This research provides theoretical contributions by extending the understanding of job satisfaction and engagement dimensions in cross-cultural joint venture contexts, while offering practical implications through targeted business solutions, including transparent career path development, compensation benchmarking, enhanced management communication strategies, and systematic training programs.